Life satisfaction of middle-aged career women in kelantan : the mediating role of job satisfaction - Siti Marziah Zakaria,; Ruzaini Ijon,; Wan Yusoff Wan Shaharuddin,; See, Soo Yin (Penerbit Universiti Kebangsaan Malaysia, 2017)
Job satisfaction is significantly related to overall attitudes towards life or life satisfaction. For most people, work is a central life activity. Full time employees spent substantial amount of time at work. Middle-aged women are working longer hours and spending less time with their families, which has led to family crisis, burn out, and depression. Thus, this study helps to determine the relationship between social support and family attachment on life satisfaction among middle-aged career women in Kelantan. It will also analyse the mediating role of job satisfaction. This study is a quantitative study, which was conducted in Kelantan. It involves 438 middle-aged career women in Kelantan. Social support, family attachment and job satisfaction were found to positively relate to life satisfaction. Moreover, job satisfaction was proven as the mediator in the relationship between social support and life satisfaction. This result indicates that life satisfaction of middle-aged career women rely significantly on job satisfaction. Job satisfaction can intervene the direction and the level of life satisfaction of middle-aged career women. This finding could be used as an input for any intervention programs and policies to uplift the well- being and quality of life of middle-aged women